Paper Tiger? Chinese Science and Home Bias in Citations - Shumin Qiu; Claudia Steinwender; Pierre Azoulay (CESifo GmbH, 2025)
We investigate the phenomenon of home bias in scientific citations, where researchers disproportionately cite work from their own country. We develop a benchmark for expected citations based on the relative size of countries, defining home bias as deviations from this norm. Our findings reveal that China exhibits the largest home bias across all major countries and in nearly all scientific fields studied. This stands in contrast to the pattern of home bias for China's trade in goods and services, where China does not stand out from most industrialized countries. After adjusting citation counts for home bias, we demonstrate that China's apparent rise in citation rankings is overstated. Our adjusted ranking places China fourth globally, behind the US, the UK, and Germany, tempering the perception of China's scientific dominance.
Keywords: I23; O30; O53; 330; home bias; China; citations; economics of science; basic research; international spillovers